A hybrid formation path planning based on A* and multi-target improved artificial potential field algorithm in the 2D random environments. (October 2022) - Tong, Xiaolong; Yu, Shanen; Liu, Guangyu; Niu, Xiaodie; Xia, Cunjun; Chen, Jianke; Yang, Zhe; Sun, Yingyi
Abstract: Traditional artificial potential field algorithm for multi-robot formation is easy to fall into local minima and the path planning efficiency is low. To this end, we propose a new method of a hybrid formation path planning based on A* and multi-target improved artificial potential field algorithm (A*-MTIAPF) that provides the optimal collision free path and improves the efficiency for multi-robot formation path planning. The A*-MTIAPF algorithm integrates global path planning and local path planning. The novelties include combining A* with the improved artificial potential field algorithm and dividing multiple virtual sub-target points on the global optimal path of A* planning. Firstly, A* algorithm is used to complete the global path planning. Secondly, the improved artificial potential field algorithm which takes multiple sub-target points divided by the global optimal path as virtual target points is used to complete local path planning by switching target points. In addition, we propose a double priority judgment control algorithm (DPJC) to solve the collision problem among multiple robots by setting double priority to determine the movement order of each robot. Then, a new experimental method is designed by using the randomly generated 2D maps to verify the effectiveness of the proposed method. The results show that our method has advantages that it solves the local minimum problem, improves the efficiency of formation path planning and avoids collision among multiple robots over existing methods. Highlights: A formation path planning algorithm combine A* and improved APF. Multiple virtual sub-target points are divided on the global optimal path. Double priority judgment control method is used to avoid collision between robots. Random maps are used for simulation to objectively verify the proposed algorithm.